Measuring Light Pollution in The Night Sky - from Technology Demonstrator to Monitoring System - Karpińska, Dominika; Kunz, Mieczysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pollution of the night sky by artificial light has now become an important element of the modern city landscape. The decline in the quality of the sky observed at night in urban areas has already been noticed even by residents unaware of its origin. A starry sky is nowadays not easy to observe even in places far from large conurbations or smaller cities.
Keywords: light pollution; automatic measurement; LoRaWAN; smart city; Industry 4.0; monitoring system